Fade - McMann, Lisa. (New York : Simon Pulse, 2009)
Using her ability to tap into other people's dreams, eighteen-year-old Janie investigates an alleged sex ring at her high school that involves teachers using the date rape drug on students.
Sequel to: Wake.
Keywords: Dreams -- Fiction; Lucid dreams -- Fiction; Undercover operations -- Fiction; Sexual abuse victims -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction